Contents & Introduction, Law Text Culture, volume 26 - Desmond Manderson (Law Text Culture, 2022)
The essays in this collection grew out of an online symposium series organized in the middle of the 2020 pandemic lockdown in Australia. We had a sense of the vital role of metaphor in how we think; vital in the twin senses of crucial and full of life. We wanted to find out more from colleagues working in disciplines as diverse as history, cultural studies, critical theory, law, and philosophy. We wanted to think about the role of metaphors in how we confront difference; in how we make sense of the world; in the political, legal, and social challenges of the world we live in. What metaphors frame our thinking and to what ends? The answers that emerged orbit around a series of underlying tensions: metaphor as necessity, opportunity, and impurity; metaphor as natural, as strategic, as tactical; metaphor as a way of living, a way of seeing, and a way of obscuring; metaphor as keeping faith and metaphor as betrayal; metaphor as critique and the critique of metaphor. In exploring these tensions, three matters of concern kept recurring, and these three themes form the structure of the collection to follow: colonialism, monsters, and disease. Each chapters focuses on one of these themes, but all convincingly draw out their interconnections and mutual implications. What is colonialism but a monstrous disease? What are these monsters but diseased colonists? What is disease but yet another colonising monstrosity?